Influence of investment activity’s features for its control - Шкіренко, Вікторія Володимирівна (Technology audit and production reserves, 2015)
Stable rising tendency of total foreign investments to Ukrainian economy and permanent increase of capital investments to national enterprises needs stable development and perfection of legislative, theoretical and methodical bases of investment control. That is why a real necessity of theoretical and practical analysis of investment control category appears. There is no clear definition of the this term in national scientists’ researches. This is a reason of investment control imperfection on all levels of economic system functioning and stable economic rising inhibition. The article reveals analysis of the main features of investment process control. The author worked out practical recommendations for investigated features classification on the specific characteristics for further determination of their influence for types, forms and subject of investment control as a part of company’s management system. Research of economic entity investment control for its tasks and comprehension substantiation has been made As a result the author has worked out her own definition of this economic category, determined its main types and forms for their correlation analysis. The necessity of investment activity features usage in economic control system developing according to goals and tasks of revision, relevant to company’s activity, internal economic conditions and environment’s characteristics is substantiated.